2010
DOI: 10.2337/db10-0245
|View full text |Cite|
|
Sign up to set email alerts
|

Acute Stimulation of White Adipocyte Respiration by PKA-Induced Lipolysis

Abstract: OBJECTIVEWe examined the effect of β-adrenergic receptor (βAR) activation and cAMP-elevating agents on respiration and mitochondrial uncoupling in human adipocytes and probed the underlying molecular mechanisms.RESEARCH DESIGN AND METHODSOxygen consumption rate (OCR, aerobic respiration) and extracellular acidification rate (ECAR, anaerobic respiration) were examined in response to isoproterenol (ISO), forskolin (FSK), and dibutyryl-cAMP (DB), coupled with measurements of mitochondrial depolarization, lipolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 53 publications
5
104
1
Order By: Relevance
“…However in human, obesity is associated with reduced RIIβ expression and PKA activity in WAT (Mantovani et al 2009). βAR-stimulated lipolysis and mitochondrial respiration are also decreased in WAT of obese patients (Yehuda-Shnaidman et al 2010). In 3T3-L1 adipocytes, it has been shown that the anchoring of PKA to AKAP is required for βAR-stimulated lipolysis (Pidoux et al 2011).…”
Section: Camp/pka In Adipose Tissuesmentioning
confidence: 99%
“…However in human, obesity is associated with reduced RIIβ expression and PKA activity in WAT (Mantovani et al 2009). βAR-stimulated lipolysis and mitochondrial respiration are also decreased in WAT of obese patients (Yehuda-Shnaidman et al 2010). In 3T3-L1 adipocytes, it has been shown that the anchoring of PKA to AKAP is required for βAR-stimulated lipolysis (Pidoux et al 2011).…”
Section: Camp/pka In Adipose Tissuesmentioning
confidence: 99%
“…12,17,18 Studies of cachexia in rodents suggest activation of thermogenesis (i.e., increased mitochondrial uncoupling of oxidative phosphorylation and elevated fatty acid b-oxidation) in brown adipose tissue 19,20 may contribute to elevated whole body lipid utilization in cachexia, at least in later stages of cachexia. 20 Additionally, recent studies in healthy rodents and human adipocytes have linked stimulation of lipolysis in white adipose tissue with increased fatty acid oxidation 21,22 and uncoupling 21,23,24 in white adipose depots. This "brown-like" adipocyte phenotype in white adipose tissue might also contribute to elevated whole body lipid utilization in cachexia and thus depletion of adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…When (post)prandial plasma levels of NEFA and triacylglycerol (TG) exceed the storage capacity of WAT [1], other tissues including the liver and muscle become overloaded with lipids, which results in insulin resistance, the key event in the pathophysiology of metabolic syndrome [2]. The important role of WAT in energy homeostasis is underscored by the findings that WAT is one of the key organs affected by calorie restriction, the most effective strategy to prolong a healthy life in several species [3], and by the fact that accumulation of body fat can be reduced through upregulation of lipid catabolism in WAT [4][5][6][7][8][9][10]. The metabolism and secretory functions of WAT are also modulated by longchain (LC) n-3 polyunsaturated fatty acids (PUFA), namely eicosapentaenoic acid (EPA; 20:5 n-3) and docosahexaenoic acid (DHA; 22:6 n-3), which exert numerous beneficial effects on health, including improvements in lipid metabolism and prevention of obesity and diabetes [11], while decreasing the rate of fatal coronary heart disease in diabetic patients who have had a myocardial infarction [12].…”
Section: Introductionmentioning
confidence: 99%